Craniofacial Venous Plexuses: Angiographic Study - Osborn, Anne G. (American Journal of Neuroradiology, 1980)
Venous drainage patterns at the craniocervical junction and skull base have been thoroughly described in the radiographic literature. The facial veins and their important anastomoses with the intracranial venous system are less well appreciated. This study of 54 consecutive normal cerebral angiograms demonstrates that visualization of the pterygoid plexus as well as the anterior facial, lingual, submental, and ophthalmic veins can be normal on common carotid angiograms. In contrast to previous reports, opacification of ophthalmic or orbital veins occurs in most normal internal carotid arteriograms. Visualization of the anterior facial vein at internal carotid angiography can also be normal if the extraocular branches of the ophthalmic artery are prominent and nasal vascularity is marked.